2010
DOI: 10.1039/b923567a
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal nDEP cages within open microwell arrays for precise positioning of cells and particles

Abstract: We present the structure of an open microwell, i.e. a microwell open at both the top and bottom ends, which enables single-cells to be handled, processed and recovered after the experiment. The microwell has a novel architecture which allows particles to be trapped and forced to interact by means of a cylindrical negative dielectrophoretic cage. Particles are aligned along a horizontal axis where the electric field minimum is placed. Arrays of open microwells are fabricated using flexible printed circuit board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A significant number of studies reported different types of DEP microfluidic devices for isolation and separation of particles based on the n‐DEP. The designs of such electrodes are parallel electrodes with an insulator between the electrodes, multipole electrodes (e.g., quadrupole, octupole), n‐DEP cages, cantilever type electrodes, planar electrodes with different shaped and geometry such as pearl‐shaped, circular, square in interdigitated type electrodes [20–28]. A lot of these electrodes were designed for concentration and immobilization of multiple particles simultaneously, rather than trapping and manipulation in single‐particle level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of studies reported different types of DEP microfluidic devices for isolation and separation of particles based on the n‐DEP. The designs of such electrodes are parallel electrodes with an insulator between the electrodes, multipole electrodes (e.g., quadrupole, octupole), n‐DEP cages, cantilever type electrodes, planar electrodes with different shaped and geometry such as pearl‐shaped, circular, square in interdigitated type electrodes [20–28]. A lot of these electrodes were designed for concentration and immobilization of multiple particles simultaneously, rather than trapping and manipulation in single‐particle level.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of these electrodes were designed for concentration and immobilization of multiple particles simultaneously, rather than trapping and manipulation in single‐particle level. For effective particle isolation using n‐DEP, an electrode capable to produce lower electric field gradient within a closed shape is more effective [26–30]. It is possible to generate a uniform lower electric gradient in a closed shape window in the electrode, which can serve as the trapping locations for the particles isolated inside the DEP device.…”
Section: Introductionmentioning
confidence: 99%
“…The DEP force is non-contact and it involves low damage to cells. However, the DEP force is not sufficient to immobilize cells during changes in a medium with high flow velocity, as seen in [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] This kind of physical problem could be found in many microfluidic applications such as polydimethylsiloxane (PDMS) microchannels with open outlets. [11,12] The novel performance of the Marangoni flow has potential applications in micropumping with a totally different mechanism from previous ones. [13,14] The T-junction is formed by a main channel and a side channel (Fig.…”
mentioning
confidence: 99%